Postcard from attendees of a scientific congress in Vienna addressed to Georg Bredig (1927)
Colleagues, acquaintances, and students of Georg Bredig (1868-1944) send him a postcard from the Congress of Natural Scientists in Vienna.
Keywords: Haber, Fritz, 1868-1934; Bredig, Georg, 1868-1944; Austria--Vienna